2021
DOI: 10.1111/and.14341
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide‐induced testicular oxidative‐inflammatory injury is accompanied by altered immunosuppressive indoleamine 2, 3‐dioxygenase in Wister rats: Influence of dietary quercetin

Abstract: This study evaluated the role of quercetin against cyclophosphamide‐induced distortion of rat testicular function. Adult rats were administered cyclophosphamide (100 mg/kg), quercetin (50 mg/kg) and in combination for seven days. Cyclophosphamide caused a significant increase in the activities of indoleamine 2, 3‐dioxygenases (IDO), tryptophan 2, 3‐dioxygenase (TDO), myeloperoxidase (MPO), and elevated the concentrations of interleukin 6 (IL‐6) and interferon‐γ (IFN‐γ). Cyclophosphamide increased testis malond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Additionally, FSH and LH play a role in regulating Leydig cell function to produce testosterone in males [ 8 ]. CP markedly reduced the serum levels of testosterone, FSH, LH, and prolactin [ 11 ], even at a single dose of 100 mg/kg [ 34 ]. The results of this study indicated that CP affected spermatogenesis by interfering with cellular processes as well as the pituitary–testicular axis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, FSH and LH play a role in regulating Leydig cell function to produce testosterone in males [ 8 ]. CP markedly reduced the serum levels of testosterone, FSH, LH, and prolactin [ 11 ], even at a single dose of 100 mg/kg [ 34 ]. The results of this study indicated that CP affected spermatogenesis by interfering with cellular processes as well as the pituitary–testicular axis.…”
Section: Discussionmentioning
confidence: 99%
“…HSP significantly enhanced the serum testosterone, FSH, LH, and prolactin levels following bisphenol A administration [ 35 , 36 ]. Also, the administration of other flavonoids, including quercetin [ 11 ] or morin [ 37 , 38 ], or rutin [ 38 ], improved serum levels of testosterone, FSH, LH, and prolactin. This could be attributed to the protective roles of flavonoids in terms of anti-inflammatory and antioxidant ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major physiological pathway of tryptophan (Trp) catabolism involves the kynurenine pathway via the action of the hepatic tryptophan‐2,3‐dioxygenase (TDO) and the ubiquitous IDO 43 . Pro‐inflammatory cytokines, IL‐6 interleukins and their accompanying oxidative biomarkers are well known to trigger the activity/expression of IDO, which usually favours the accumulation of kynurenine and LPO that is associated with testicular injury 9 . Our findings demonstrated that EtOH exposure aggravated IDO expression/activity in the testes.…”
Section: Discussionmentioning
confidence: 99%